The role of Elateriospermum tapos yoghurt in mitigating high-fat dietary cause of maternal obesity—an experimental study - Naomi, Ruth; Rusli, Rusydatul Nabila Mahmad; Othman, Fezah; Balan, Santhra Segaran; Abidin, Azrina Zainal; Embong, Hashim; Teoh, Soo Huat; Jasni, Azmiza Syawani; Jumidil, Siti Hadizah; Bahari, Hasnah; Yazid, Muhammad Dain (Frontiers in Endocrinology, 2023)
Maternal obesity is the key predictor for childhood obesity and many other complications over time. Medicinal plant considered to be the safe and best option and at the same time probiotic consumption during pregnancy provides beneficial effects for both mum and the child. Current research have shown that Elateriospermum tapos (E.tapos) yoghurt is safe to consume and comprise of many bioactive compounds that can exerts anti-obesity effect. Thus, this study has been de-signed to study the role of E.tapos yoghurt in mitigating maternal obesity. In this study, a total of 48 female Sprague Dawley (SD) rats were assigned to 6 groups, eight rats per group and obesity induced over 16 weeks with a high fat diet (HFD) pellet. On the 17th weeks the rats allowed to mate and pregnancy was confirmed through vaginal smear. The obese induced group was fur-ther divided into negative and positive controls groups, followed by 3 different concentration of (5, 50, and 500 mg/kg) E.tapos yoghurt treatment group. The changes in body weight, calorie in-take, lipid profile, liver profile, renal profile, and histopathological analysis were done on postnatal day (PND) 21. The results shows that highest concentration of E.tapos yoghurt (HYT500) supplemented group shows gradual reduction in body weight and calorie intake on PND 21 and modulates the lipid level, liver, and renal enzymes to normal level similar to normal group. In histological analysis, HYT500 reverse the damage caused by HFD in liver, colon, and reverse the adipocytes hypertrophy in retroperitoneal white adipose tissue, and visceral fat. In conclusion, supplementation of E.tapos yoghurt during gestational period up to weaning effective in gradual weight loss in maternal obese dams at 500 mg/kg supplemented group in this study.